1991
DOI: 10.1111/j.1600-0404.1991.tb05002.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypersomnia in dystrophia myotonica: a neurophysiological and immunogenetic study

Abstract: Ten patients with dystrophia myotonica (8 adults and 2 prepubertal children), from three unrelated families, were investigated for diurnal sleepiness, using a sleep questionnaire and multiple sleep latency test (MSLT). Immunogenetic study was also carried out to assess the involvement of HLA region genes in modulating susceptibility to excessive diurnal sleepiness (EDS). EDS was reported by 5 patients and confirmed in each case by MSLT. In the whole patients group, mean daytime sleep latency was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…Discrepancies in the quality of nocturnal sleep in DM1 have long been documented, with self-reports of either sleep disruption2 4 14 or deep, restorative sleep 5 15 16. Polysomnographic (PSG) studies yielded contradictory results, either showing indices of sleep fragmentation4 17 or normal sleep architecture features5 15 16 18 19 with810 or without15 17 sleep-onset rapid-eye movement (REM) periods (SOREMPs).…”
mentioning
confidence: 99%
“…Discrepancies in the quality of nocturnal sleep in DM1 have long been documented, with self-reports of either sleep disruption2 4 14 or deep, restorative sleep 5 15 16. Polysomnographic (PSG) studies yielded contradictory results, either showing indices of sleep fragmentation4 17 or normal sleep architecture features5 15 16 18 19 with810 or without15 17 sleep-onset rapid-eye movement (REM) periods (SOREMPs).…”
mentioning
confidence: 99%
“…However, the ptosis, myopathic facies and dysarthric speech noted in DM can give a false impression of somnolence, and therefore the true extent of the problem could be overestimated. A variety of factors including affective state, respiratory [8][9][10][11][12][13][14] and generalised skeletal muscle weakness, abnormalities in central and peripheral respiratory control [10,13,[15][16][17][18] and in arousal [19][20][21][22] might be associated with sleepiness in DM. Somnolence is recognised as a symptom which causes significant disability and handicap in the general population [23].…”
mentioning
confidence: 99%
“…An intrinsic hypersomnia may therefore be associated sharing with narcolepsy a short sleep latency and the presence of sleep onset REM periods during the Multiple Sleep Latency Test. However, few studies revealed the absence of clear association between DM1 and HLA DQB1* 0602 as in narcolepsy but without any design to clearly establish an association between DMI with sleep-onset REM hypersomnia and HLA class II subtype [34]. A recent study noted the absence of difference between CSF hypocretin levels between 38 DM1 patients and 33 normal controls [36].…”
Section: Hypersomnias Associated With Neurological Condition: Myotonimentioning
confidence: 97%
“…Amplification is frequently observed after parent-to-child transmission, but extreme amplifications are not transmitted through the male line. DM1 has long been recognized for its sleep disturbances, and excessive daytime sleepiness is the commonest complaint with multifactorial etiologies including sleep fragmentation, central and obstructive sleep apneas, and dysregulation of REM sleep with frequent abnormal REM sleep pressure [33,34]. An intrinsic hypersomnia may therefore be associated sharing with narcolepsy a short sleep latency and the presence of sleep onset REM periods during the Multiple Sleep Latency Test.…”
Section: Hypersomnias Associated With Neurological Condition: Myotonimentioning
confidence: 99%